Mitochondrial complex I subunit NDUFS8.2 modulates responses to stresses associated with reduced water availability - Zsigmond, Laura (Plant physiology and biochemistry : PPB, 2024)
Copyright © 2024 The Authors. Published by Elsevier Masson SAS.. All rights reserved.